Interleukin-6 and pulmonary hypertension: from physiopathology to therapy - Xu, Wei-Jie; Wu, Qiong; He, Wen-Ni; Wang, Shang; Zhao, Ya-Lin; Huang, Jun-Xia; Yan, Xue-Shen; Jiang, Rong (Frontiers in Immunology, 2023)
Pulmonary hypertension (PH) is a progressive, pulmonary vascular disease with high morbidity and mortality. Unfortunately, the pathogenesis of PH is complex and remains unclear. Existing studies have suggested that inflammatory factors are key factors in PH. Interleukin-6 (IL-6) is a multifunctional cytokine that plays a crucial role in the regulation of the immune system. Current studies reveal that IL-6 is elevated in the serum of patients with PH and it is negatively correlated with lung function in those patients. Since IL-6 is one of the most important mediators in the pathogenesis of inflammation in PH, signaling mechanisms targeting IL-6 may become therapeutic targets for this disease. In this review, we detailed the potential role of IL-6 in accelerating PH process and the specific mechanisms and signaling pathways. We also summarized the current drugs targeting these inflammatory pathways to treat PH. We hope that this study will provide a more theoretical basis for targeted treatment in patients with PH in the future.